Temporal Boundaries of an Arbitration Agreement as a Prerequisite for Submitting a Dispute to International Commercial Arbitration - KUZNIETSOVA, Nataliia S.; PRYTYKA, Yurii D.; KHOMENKO, Mykhailo M. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
One of the most effective methods of resolving legal disputes is the development of international commercial arbitration. The signing of the arbitration agreement is a key factor in the submission of the dispute to arbitration. The purpose of this study is to identify the main approaches to understanding the term of the arbitration agreement and to outline the main reasons for considering this aspect of the arbitration agreement. For the purpose of this study, general scientific and special methods, such as comparative-legal method, method of analysis, method of synthesis, were used. As a result of the research, the principles and interpretation of the autonomy of the arbitration agreement, different legal consequences and different legal nature of the expiration of limitation period and defects of the temporal terms of the arbitration agreement, ways of determining the term of the arbitration agreement have been determined. The authors conclude that the question of the applicability of the arbitration agreement to a particular contract should be determined on the basis of substantive provisions of a main contract and an arbitration agreement.